2018
DOI: 10.1007/978-3-030-00689-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Conversion of Mild Cognitive Impairments to Alzheimer’s Disease and Exploring Impact of Neuroimaging

Abstract: Nowadays, a lot of scientific efforts are concentrated on the diagnosis of Alzheimers Disease (AD) applying deep learning methods to neuroimaging data. Even for 2017, there were published more than a hundred papers dedicated to AD diagnosis, whereas only a few works considered a problem of mild cognitive impairments (MCI) conversion to AD. However, the conversion prediction is an important problem as approximately 15% of patients with MCI converges to AD every year. In the current work, we are focusing on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…We employed 3D MRI instead of 2D multi-slice MRI. Previous studies have also reported MCI to AD prediction using a sequential full volume 3D architecture have obtained BAs of 0.75 (Basaia et al, 2019) and0.73 (Wen et al, 2020), while a study using residual architecture showed a resulting BA of 0.67 (Shmulev & Belyaev, 2018) but did not involve longitudinal MRI data. Some studies used predetermined 3D patches uniformly sampled across the brain (Lian et al, 2018;Liu et al, 2018;Wen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed 3D MRI instead of 2D multi-slice MRI. Previous studies have also reported MCI to AD prediction using a sequential full volume 3D architecture have obtained BAs of 0.75 (Basaia et al, 2019) and0.73 (Wen et al, 2020), while a study using residual architecture showed a resulting BA of 0.67 (Shmulev & Belyaev, 2018) but did not involve longitudinal MRI data. Some studies used predetermined 3D patches uniformly sampled across the brain (Lian et al, 2018;Liu et al, 2018;Wen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning classification amongst normal cognition (NC), MCI and AD based on magnetic resonance imaging (MRI) data have been reported ( Cheng et al, 2017 ; Korolev et al, 2017 ; Wen et al, 2020 ). By contrast, there are comparatively fewer studies that reported prediction of MCI to AD conversion using deep learning of MRI data ( Lian et al, 2018 ; Lin et al, 2018 ; Liu et al, 2018 ; Shmulev & Belyaev, 2018 ; Basaia et al, 2019 ; Wen et al, 2020 ). A few ML studies used extracted brain structures or cortical thicknesses, and some used 3D patches from predetermined locations across the brain, but not whole-brain MRI data, to predict MCI to AD conversion ( Lian et al, 2018 ; Liu et al, 2018 ; Wen et al, 2020 ).…”
Section: Backgroudmentioning
confidence: 99%
“…Studies in this section aim at predicting the progression of patients in a pre-defined time frame. The length of this time frame depends on the disease studied: a few minutes for epilepsy [189] to several years for multiple sclerosis [190] or Alzheimer's disease [191][192][193][194][195].…”
Section: Fixed-time Classificationmentioning
confidence: 99%
“…Therefore, in this section we will only focus on transfer learning between these two tasks. Four possibilities were explored: i) transferring weights from AD versus HC and then fine-tuning on pMCI versus sMCI [191,192]; ii) transferring from a classification with the first class mixing AD and pMCI labels and the second class HC and sMCI labels, and then fine-tuning on pMCI versus sMCI [193]; iii) directly testing the network on pMCI and sMCI patients without fine-tuning after learning the AD versus HC classification [195]; and iv) directly learning sMCI versus pMCI classification [194]. It is important to note that the definition of the labels may vary between studies.…”
Section: Fixed-time Classificationmentioning
confidence: 99%
“…Deep learning classification amongst normal cognition (NC), MCI and AD based on magnetic resonance imaging (MRI) data have been reported (Cheng et al 2017;Korolev et al 2017;Wen et al 2020). By contrast, there are comparatively fewer studies that reported prediction of MCI to AD conversion using deep learning of MRI data (Lian et al 2018;Lin et al 2018;Liu et al 2018;Shmulev & Belyaev 2018;Basaia et al 2019;Wen et al 2020). A few ML studies used extracted brain structures or cortical thicknesses, and some used 3D patches from predetermined locations across the brain, but not whole-brain MRI data, to predict MCI to AD conversion (Lian et al 2018;Liu et al 2018;Wen et al 2020).…”
Section: Introductionmentioning
confidence: 99%